2020
DOI: 10.1016/j.heliyon.2020.e05160
|View full text |Cite
|
Sign up to set email alerts
|

Educational Robotics for children with neurodevelopmental disorders: A systematic review

Abstract: This paper aims to provide a critical review of the studies dealing with Educational Robotics for children with Neurodevelopmental Disorders. We aimed to investigate whether in the literature there is a sound evidence that activities with robots improve the abilities and performances of children with special needs. This paper explores the methodological aspects as well as the outcomes of the selected studies to provide a clear picture of the state-of-the-art on this topic. After a systematic search in the onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 46 publications
2
53
0
Order By: Relevance
“…In a recent review of the literature on ER for students with neurodevelopmental disorders, the authors [10] reported that from most studies it emerged that students (from 3 to 19 years of age) showed improvements in school performance or in class involvement, or in communication/interaction with peers. For instance, in the work of González-González and colleagues [11] aimed at assessing the cognitive, social and emotional development of students with Down syndrome (DS) in primary and secondary education, a positive impact of KIBO robots on students' engagement was reported.…”
Section: Robotics In a Classroom With Special Needs Studentsmentioning
confidence: 99%
“…In a recent review of the literature on ER for students with neurodevelopmental disorders, the authors [10] reported that from most studies it emerged that students (from 3 to 19 years of age) showed improvements in school performance or in class involvement, or in communication/interaction with peers. For instance, in the work of González-González and colleagues [11] aimed at assessing the cognitive, social and emotional development of students with Down syndrome (DS) in primary and secondary education, a positive impact of KIBO robots on students' engagement was reported.…”
Section: Robotics In a Classroom With Special Needs Studentsmentioning
confidence: 99%
“…The usability of the setup was good for the therapist and the child, and the system was not invasive even after weeks of sessions, showing the promise of robotics in education ( 45 ). A formal evaluation of acceptability is planned with an improved version of the Dynamico–Nao setup in both occupational therapy sessions and in a classroom for children with special needs ( 15 ). Although several feature scores improved during R's treatment, it was not the case for the time to finish the tilt activity, which did not significantly decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the approaches to ICTs in education have been divided into “Learning about ICTs” and “Learning with ICTs,” in other words, between “Education in ICTs” and “ICTs for Education.” The former approach concerns technical, robotics-oriented education, while the latter implies teaching different subjects (technical and nontechnical) through ICTs. For example, in the case of robotics, it is of paramount importance to distinguish between “ICTs used for CSN” and “ICTs used by CSN” ( 15 ). Most studies in the field ICT and learning regard (1) reading, spelling, math, and writing acquisition when they come from education [e.g., 17, 18] or (2) ASD when they come from child psychiatry ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, ARDs are used as learning robots for activities at different environments: (a) as part of school curricula; (b) for therapy interventions; and (c) for other activities that take place at home and in communities. In a recent systematic review about educational robotics for children with NDDs [ 10 ], the authors reported that the most common learning robots are Bee-Bot, KIBO, Lego MINDSTORMS and NAO NextG. The study concluded that learning robots improve performance in learning objectives, and the children’s engagement in learning activities and communication/interactions with peers.…”
Section: Related Workmentioning
confidence: 99%